THE JUDGE’S ROLE OF SURVEILLANCE OF DEPRIVATION OF LIBERTY IN THE EXECUTION OF THE CUSTODIAL PENALTIES - Dantes MARCOVICI (Challenges of the Knowledge Society)
In this study, I decided to analyze the activity of the judge of surveillance of deprivation of liberty in relation to the amendments made by Law no. 254/2013 on the execution of sentences and custodial measures ordered by the court during the criminal trial, published in the Official Gazette no. 514 of August 14, 2013. I will also analyze its role, both in terms of the powers of an administrative nature, especially those with administrative-jurisdictional nature in establishing and changing the arrangements for enforcement and custodial, educational measures for the solving of the complaints regarding the disciplinary sanctions and the complaints regarding the exercise of the rights provided by Law no. 254/2013;